FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN PEMBAYARAN DIVIDEN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Muhammad Akmal Alauddin; Henny Setyo Lestari (Business, Economics dan Entrepreneurship, 2022)
Dividends are an important aspect, both for investors and the company itself. Not all companies will pay dividends to shareholders. Therefore, there are factors that influence the dividend payment policy. In this study, researchers used factors such as profitability, investment opportunities, free cash flow, leverage, liquidity, firm size, and ownership structure consisting of institutional and managerial ownership. This study aims to determine the significance of the influence of the factors that can affect the dividend payout ratio in manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period. This study used purposive sampling as a sampling technique and obtained as many as 30 companies as samples, as well as descriptive statistical analysis and panel data regression as data analysis methods. The results show that the ownership structure consisting of institutional and managerial ownership has a significant negative effect on the dividend payout ratio of manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period.